Lithology Identification Using Electrical Resistivity Tomography Case Study: OAL’s Construction Site - Erlangga Ibrahim F.; Andri Yadi Paembonan; Cahli Suhendi; Hikhmadhan Gultaf; Virgian Rahmanda; Lea Kristi Agustina; Hendra Saputra; Maria R.P. Sudibyo; Reza Rizki (Journal of Multidisciplinary Academic, 2019)
Observatory Astronomy Lampung construction site is located at Mountain Betung, North – West of Lampung City. From geomorphology investigation, Mount Betung landscaped classified as volcanic mountain with pyroclastic flow mountaincharacteristics. Geological setting of this area showed those dominant lithology is pyroclastic, including andesite and breccia rocks. These feature correlate with our investigation around OAL construction site. We applied electrical resistivity tomography to investigate subsurface soil electrical properties. The result indicated that there are two different lithology, high resistivity in the top soil and low resistivity below. High resistivity suspected as pyroclastic deposit with a lot of volcanic rocks fragment, whereas the low resistivity suspect as volcanic deposit with high – saturated water, which indicated as clay